2009
DOI: 10.1051/limn/09001
|View full text |Cite
|
Sign up to set email alerts
|

Food-web structure and functioning of temperate and tropical lakes: A stoichiometric viewpoint

Abstract: -Difficulties to simply transfer trophic cascade theory from temperate to tropical lakes are now well recognized. Many mechanisms trying to explain top-down divergences between these systems have been proposed, such as lack of key species of herbivorous zooplankton, absence of seasonality in fish reproduction, cyanobacteria development, or differences in fish foraging behaviour. Very few studies have considered bottom-up mechanisms, in particular differences in nutrient recycling and nutrient limitation betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 48 publications
1
11
0
Order By: Relevance
“…However, fish-mediated nutrient recycling did not enhance the cyanobacteria biomass, because phytoplankton growth in our study was P-limited, and tilapia release nutrients at high N to P ratios (Danger et al, 2009). This is confirmed by the higher ammonium/ nitrate and lower phosphate concentrations in the fish treatment in comparison to the control, from the middle to the end of the experiment.…”
Section: Discussionsupporting
confidence: 53%
“…However, fish-mediated nutrient recycling did not enhance the cyanobacteria biomass, because phytoplankton growth in our study was P-limited, and tilapia release nutrients at high N to P ratios (Danger et al, 2009). This is confirmed by the higher ammonium/ nitrate and lower phosphate concentrations in the fish treatment in comparison to the control, from the middle to the end of the experiment.…”
Section: Discussionsupporting
confidence: 53%
“…Presumably, the cascading effects of predatory fish are weaker in tropical than in temperate lakes (Jeppesen et al 2010;Gelós et al 2010;Danger et al 2009), which has been attributed to: (1) higher abundance and diversity of small fish species with continuous reproduction, (2) higher fish aggregation within the vegetation, and (3) more omnivory by fish and less specialist piscivory (Lazzaro 1997;Jeppesen et al 2007Jeppesen et al , 2010. However, the trophic dynamics and role of fish in warm lakes are much less well understood than for temperate lakes (Jeppesen et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…However, a decrease in the biomass of planktonic primary producers has sometimes been observed without any increase in the grazing capacity by zooplanktonic communities (e.g. Danger et al 2009). This suggests that, in addition to modification of zooplankton communities, other processes could be involved in the reduction of phytoplankton biomass when fish are manipulated.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, several studies demonstrated that changes in fish biomass induced complex changes that can have important impacts on lake functioning. By manipulating the food web through the presence or absence of fish in a long-term mesocosm experiment, Danger et al (2008Danger et al ( , 2009) demonstrated that the stoichiometric characteristics (C:N:P ratios) of biofilms and zooplankton differed between fish and fishless enclosures. Such changes might modify the efficiency of predator-prey interactions and nutrient balance within aquatic ecosystems.…”
Section: Introductionmentioning
confidence: 99%